KETERLIBATAN TENTARA PELAJAR PADA SERANGAN UMUM EMPAT HARI DI SURAKARTA TAHUN 1949 - Ivan Prapanca Wardhana; Muhadi Muhadi; Ageng Sanjaya (Universitas Veteran Bangun Nusantara, 2019)
This study aims to determine the beginning of the Four-Day General Attack in Surakarta in 1949, to know the role and involvement of the Student Army in the 1949 General Four-Day Attacks in Surakarta both before the fighting, when the battle took place until the battle ended and to know how the influence The Four Day General Attack in Surakarta in 1949 against the recognition of the sovereignty of the Republic of Indonesia by the Government of the Kingdom of the Netherlands. Research and writing on the occurrence of the Four Day General Attacks in Surakarta in 1949 using the Historical Research Method with a Social Approach. This approach is used in describing past events, so that the social aspects of the events examined will be revealed in it. In accordance with the subject matter to be discussed, the method used is the Historical Research Method. From this research, one conclusion can be drawn that the beginning of the Four-Day Battle in Surakarta was due to a reaction from the launch of Military Aggression II where the Dutch troops entered the city of Solo, and the purpose of the Four-Day Battle in Surakarta was to get a position and field during cease fire applied. In addition, the students who joined the Student Army Force also had an important role in the course of the General Attacks in addition to fighting and holding escorts in the surrender of the City of Solo. After the expulsion of the Dutch forces from the city of Solo, the result of a 4-day General Attack benefited the Republic both in the military and in the political field. In the Round Table Conference, the Dutch were forced to admit that the Republic of Indonesia's fighters had a very strong position in the City of Solo and surrendered the sovereignty of the Republic of Indonesia.